Oral Health-Related Quality of Life (OHRQoL) in Menopausal Medically Compromised Patients at RSGM UMY - Allifiah, Bella Pardian Nur; Triswari, Dyah; Hartanti (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Menopause is the time of life when a woman’s ovaries stop producing hormones and the menstrual periods stop. Menopausal women experience a decrease in the function of estrogen and progesterone hormones as a sign of the stopped fertile period for women. Menopause causes hormonal change and systemic conditions for menopausal woman. The systemic condition from hormonal change often makes medically compromised in menopausal woman. These conditions can be related to quality of life-related dental and oral health. This study aims to describe Oral Health-Related Quality of Life (OHRQoL) in menopausal patients with medically compromised at RSGM UMY. This type of research used is descriptive observational with cross-sectional design. 110 participants menopausal women with medically compromised  45 years were given were given the OHIP-14 questionnaire using interview techniques. This study used Oral Health Impact Profile-14 (OHIP-14) questionnaire instruments with frequency data distribution analysis. 40 respondents (36.6%) have good quality of life, 66 respondents (60%) have moderate quality of life, and as many as 4 respondents (3.6%) have poor quality of life. The respondents mayority felt complaints on the physical disturbance dimension of discomfort when chewing. Based on OHIP-14 questionnaire showed that most of the respondents have moderate quality of life (60%).